Correlativity of Serbian Language and Literature and Religious Teaching Contents - Milovanović, Boško Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The educational system needs to be based on the development of personality and realization of its integrity. Therefore, by analysing and comparing the curricula of the two subjects – Serbian Language and Literature and Religious Education – in junior grades (1–4) of primary school, we ascertained certain common goals and identified the elements which facilitate their realization and those which make it difficult. We observed the need for a stronger connection between the set goals and the expected outcomes of learning in the curricula of the two subjects, and education in general, with special focus on achieving and nurturing freedom, as well as ethical values and virtues. We exemplified the importance of didactic-methodical apparatus in teaching reading and text analysis by using a fairy tale Selfish Giant by Oscar Wilde.